Assessing the potential impact on health of the UK's future relationship agreement with the EU: analysis of the negotiating positions. Issue 3 (3rd July 2021) - Fahy, Nick; Hervey, Tamara; Dayan, Mark; Flear, Mark; Galsworthy, Mike; Greer, Scott; Jarman, Holly; McKee, Martin
Abstract: While policy attention is understandably diverted to COVID-19, the end of the UK's post-Brexit 'transition period' remains 31 December 2020. All forms of future EU−UK relationship are worse for health than EU membership, but analysis of the negotiating texts shows some forms are better than others. The likely outcomes involve major negative effects for NHS staffing, funding for health and social care, and capital financing for the NHS; and for UK global leadership and influence. We expect minor negative effects for cross border healthcare (except in Northern Ireland); research collaboration; and data sharing, such as the Early Warning and Response System for health threats. Despite political narratives, the legal texts show that the UK seeks de facto continuity in selected key areas for pharmaceuticals, medical devices, and equipment [including personal protective equipment (PPE)], especially clinical trials, pharmacovigilance, and batch-testing. The UK will be excluded from economies of scale of EU membership, e.g. joint procurement programmes as used recently for PPE. Above all, there is a major risk of reaching an agreement with significant adverse effects for health, without meaningful oversight by or input from the UK Parliament, or other health policy stakeholders.